TEACHERS’ PERCEPTION ON HIDDEN CURRICULUM AT SMP GAJAH MADA MEDAN - Nenni Sinaga; Indris Tiani Telambanua; Sahlan Tampubolon3 (Institute of Computer Science (IOCS), 2022)
The hidden curriculum is not programmatically formulated in the formal curriculum, but its existence has an effect on building student character. In a hidden place in the curriculum, a teacher is an important figure in the success of creating or shaping character and personality. The relationship between teachers and students must be harmonious, so that the goal of creating the right attitude in students is achieved effectively without hindrance. This study aims to explore teachers' opinions about the hidden curriculum and its effect on the good character of SMP Gajah Mada students. This qualitative research uses data collection techniques by giving questionnaires to informants, namely Gajah Mada Middle School teachers, and observation. curriculum, integrated into the teaching and learning process, hidden curriculum is important because it forms good student character, said the teacher is an example, and effective to use. Regarding the teacher's opinion about the effectiveness of the hidden curriculum in developing student character, said the students experienced several changes, such as; students have good character, are polite, respect teachers and respect each other. conscious teacher assessment, and students learn from events. Meanwhile, from the results of class observation analysis, students already have good character, such as following the teacher's directions. From the analysis it can be seen that teachers and schools are trying to form good character in students at school and the surrounding environment.